1994
DOI: 10.1037/0735-7044.108.1.19
|View full text |Cite
|
Sign up to set email alerts
|

NMDA processes mediate anterograde amnesia of contextual fear conditioning induced by hippocampal damage: Immunization against amnesia by context preexposure.

Abstract: Hippocampal lesions in rats produce both a retrograde and an anterograde amnesia of contextual fear conditioning. The present experiments examined the anterograde deficit in context conditioning. The deficit produced by electrolytic hippocampal lesions was apparent when training occurred on 7, 14, or 28 days following surgery, confirming the durability of the amnesia. The role of the hippocampus in context conditioning may be related to an NMDA (N-methyl-D-aspartate) receptor-mediated process. Both NMDA hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
206
2
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(230 citation statements)
references
References 33 publications
21
206
2
1
Order By: Relevance
“…whereas tone conditioning requires the sampling of only one cue (e.g., Rudy 1996;Anagnostaras et al 1995). This is still somewhat similar to the role we have proposed for the hippocampus in contextual fear conditioning, which we have argued forms the contextual CS by assembling multiple cues into a single spatial or configural representation Young et al 1994;Maren et al 1998;Frankland et al 1998;Anagnostaras et al 1999). Nonetheless, ruling out the less exciting possibility that scopolamine produced deficits through purely sensory disturbance will require further investigation.…”
Section: Scopolamine and Cs Processingsupporting
confidence: 70%
See 2 more Smart Citations
“…whereas tone conditioning requires the sampling of only one cue (e.g., Rudy 1996;Anagnostaras et al 1995). This is still somewhat similar to the role we have proposed for the hippocampus in contextual fear conditioning, which we have argued forms the contextual CS by assembling multiple cues into a single spatial or configural representation Young et al 1994;Maren et al 1998;Frankland et al 1998;Anagnostaras et al 1999). Nonetheless, ruling out the less exciting possibility that scopolamine produced deficits through purely sensory disturbance will require further investigation.…”
Section: Scopolamine and Cs Processingsupporting
confidence: 70%
“…Pre-training intra-cerebral, intra-hippocampal, or intra-amygdalar infusion of APV blocks contextual fear, whereas post-training administration does not (Kim et al 1991;Fanselow et al 1994;Young et al 1994;Maren et al 1996b;Campeau et al 1992). Thus, the effects of scopolamine appear to be similar the effects of the NMDA receptor antagonist APV.…”
Section: Scopolamine Compared With Nmda Receptor Antagonismmentioning
confidence: 93%
See 1 more Smart Citation
“…The percentage of changed pixels between two adjacent 1-s quarter images recorded from a box was used as a measure of activity (for further details, see Richmond et al, 1998). Freezing is commonly identified as cessa-tion of any movement except for respiratory movements (e.g., Fanselow et al, 1994;Young et al, 1994). If the percentage of changed pixels between two adjacent 1-s images was Ͻ0.05%, this corresponded well to such movement cessation, and the behavior of the rat was scored as "freezing" for the respective second.…”
Section: Automated Measurement Of Activity and Freezingmentioning
confidence: 99%
“…It is still commonly held, however, that the dorsal hippocampus, which indeed may differ functionally from the ventral hippocampus (Moser and Moser, 1998;Zhang et al, 2002), contributes to contextual fear conditioning by supporting a unified context representation, but is not required for fear conditioning to tone (Fanselow, 2000;Gale et al, 2001;Rudy and O'Reilly, 2001;Wallenstein and Vago, 2001; but see Maren et al, 1997). In particular, fear conditioning to context, similar to spatial and episodic-like learning (Morris et al, 1989;Steele and Morris, 1999;Lee and Kesner, 2002; but see Cain, 1997), has been suggested to require processes mediated by N-methyl-D-aspartate (NMDA)-type glutamate receptors in the dorsal hippocampus, and prevalent concepts of fear conditioning to context imply a central contribution of NMDA receptor-mediated synaptic plasticity in the dorsal hippocampus to context representa-tion Young et al, 1994;Anagnostaras et al, 2001;Stiedl et al, 2000;Gale et al, 2001). However, although we recently provided respective data for the ventral hippocampus (Zhang et al, 2001), it remains to be demonstrated directly that blockade of NMDA receptors in the rat dorsal hippocampus impairs only fear conditioning to context, but not to tone.…”
Section: Introductionmentioning
confidence: 99%